Effect of carbendazim on mycelial growth and extracellular enzymes of Pleurotus sajor-caju and Trichoderma viride
Carbendazim (methyl-2-benzimidazole carbamate) stimulated the mycelial growth of Pleurotus sajor-caju (Fr.) Sing. at low concentrations (5 and 10 ppm) but inhibited at 25 ppm and above with complete growth inhibition at 100 ppm. Though its effect on total production of extracellular laccase, endoglucanase and xylanase followed the pattern, more or less, of mycelial growth but at sublethal doses (25 and 50 ppm), decline in specific activity of laccase was accompanied with 2 to 3 fold elevation in the specific activities of endoglueanase and xylanase. Laeease and filter paper activity (FPA) were used as growth marker enzymes of P. sajor-caju and T. viride respectively. T. viride completely inhibited the growth of P. sajor-caju if inoculated together but did not affect it if inoculated after allowing the latter to grow for 7 or more days. Carbendazim at 5 ppm completely inhibited T. virlde and stimulated P. sajor-caju in mixed cultures. Findings are of applied significance in prevention and control of T. viride, a common weed mould in oyster mushroom (P. sajor-caju